Housing Conditions Contribute to Underweight in Children: An Example From Rural Villages in Southeast Sulawesi, Indonesia - Tasnim Tasnim; Gouranga Dasvarma; Lillian Mwanri (Korean Society for Preventive Medicine, 2017)
Objectives The prevalence of underweight in children under 5 years of age is anomalously high in Konawe District, Southeast Sulawesi Province, Indonesia. This state of affairs may be related to poor housing conditions, such as limited access to clean water, the absence of a sanitary latrine, and the use of poor housing materials. Therefore, this study aimed to examine the effect of housing conditions on underweight in under-5 children in Konawe District. Methods This study was conducted in 2013 in 5 health centres in Konawe District, Southeast Sulawesi Province, and used a case-control study design. The study recruited 400 under-5 children, including 100 of whom were cases and 300 of whom were age-matched controls (1:3). Cases were underweight children, while the controls were children with a normal nutritional status. The independent variables were the availability and types of water and latrine facilities and housing materials (roof, wall, and floor). The statistical analysis used Cox regression. Results A lack of water availability (odds ratio [OR], 5.0; 95% confidence interval [CI], 2.7 to 9.5; p<0.001), a lack of latrine availability in the home (OR, 2.5; 95% CI, 1.5 to 4.0; p<0.001), and poor-quality roofing materials (OR, 1.7; 95% CI, 1.1 to 2.7; p<0.02) significantly contributed to underweight in children. In contrast, the walls and the floors did not contribute to under-5 year children being underweight (p=0.09 and p=0.71, respectively). Conclusions Sanitation facilities and roofing were identified as important factors to address in order to improve children's nutritional status. Children's health status was directly impacted by food intake via their nutritional status.